Seasonal residual activity in adult familial Mediterranean fever: a longitudinal observational study - DURUÖZ, MEHMET TUNCAY (My University, 2022)
Although it is assumed that cold exposure triggers inflammation in patients with familial Mediterranean fever (FMF), seasonal differences in FMF have not yet been investigated. This study aims to investigate the association of seasonal changes with the frequency of attacks, disease severity, and subclinical inflammation in FMF. This longitudinal study examined adult patients with FMF on an established treatment followed up for at least 1 year in Istanbul. Clinical characteristics, medications, intraseasonal attacks counts, arthralgia and arthritis, disease severity, and the subclinical inflammation parameters were recorded covering four seasons. Friedman\"s and Cochran\"s Q tests were used to analyze changes in the above-mentioned data over seasons. Additionally, all attacks experienced in each season were added, and interseasonal differences were compared with the Chi-square goodness-of-fit test. Data for 240 observations (60 patients) were analyzed. The mean age and disease duration were 39.78 (SD 11.91) and 10 (IQR 6-22.75) years, respectively. The comparison of medians for four seasons did not show any statistical differences in terms of attack frequency, disease severity parameters, markers of subclinical inflammation, and the presence of arthralgia and arthritis. The total number of intraseasonal attacks experienced by patients differed among the seasons (p = 0.023), with a higher count in winter. Adult individuals with established FMF are more likely to experience attacks in winter than summer, but this difference may not be seen in the general parameters of disease activity/severity. This result supports the notion that there is a pronounced residual activity in winter.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; Familial Mediterranean fever; Seasons; Climate; Cold temperature; Arthritis; VITAMIN-D LEVELS; RHEUMATOID-ARTHRITIS; DISEASE-ACTIVITY; WEATHER CONDITIONS; IN-SEASON; ASSOCIATION; SEVERITY; GENE; Familial Mediterranean fever; Seasons; Climate; Cold temperature; Arthritis